Application of Student Team Achievement Division (STAD) in Improving Students Activities and Learning Achievements - Aslamiyah, Mughiz Suwaybatul; Imtiyaza, Muhammad Iffat (Islamic Journal of Integrated Science Education (IJISE), 2022)
This experiment aims to describe the results of the application of the STAD learning model in increasing physics learning activities and achievements. The subjects studied were students of class VII-1 of Kediri State Islamic Junior High School 2. This study uses a qualitative method with the type of CAR (Classroom Action Research). The research subjects in this study were students of class VII-1 even semester 2018/2019 academic year total 31 students. The results of data analysis in cycle 1 showed that student achievement had not reached the passing standard and student activity was still in the low category. While the results of data analysis in cycle 2 showed that student achievement had reached the passing standard and student activities had increased in all aspects except for the aspects of oral activities, drawing activities, and mental activities which had not yet reached the standard passing indicators. Thus, it can be concluded that the application of the STAD model can increase student activity and achievement.